2021
DOI: 10.1016/j.apsb.2020.05.004
|View full text |Cite|
|
Sign up to set email alerts
|

Development of small-molecule tropomyosin receptor kinase (TRK) inhibitors for NTRK fusion cancers

Abstract: Tropomyosin receptor kinase A, B and C (TRKA, TRKB and TRKC), which are well-known members of the cell surface receptor tyrosine kinase (RTK) family, are encoded by the neurotrophic receptor tyrosine kinase 1, 2 and 3 ( NTRK1, NTRK2 and NTRK3 ) genes, respectively. TRKs can regulate cell proliferation, differentiation and even apoptosis through the RAS/MAPKs, PI3K/AKT and PLC γ pathways. Gene fusions involving NTRK act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 108 publications
(101 reference statements)
0
56
0
1
Order By: Relevance
“…For example, among brain tumors, glioblastoma, pilocytic astrocytoma, and pontine glioma can show gene fusions involving NTRK2 or NTRK3 [63,87,142,143]. A number of small-molecule acting as pan-Trk inhibitors are currently being evaluated in clinical trials [144][145][146]. A recent phase 1 and 2 clinical study examining the effects of the pan-Trk inhibitor larotrectinib in children and adults with various types of peripheral solid cancers harboring NTRK gene fusions found pronounced and durable responses regardless of patient age or tumor type [147].…”
Section: Discussionmentioning
confidence: 99%
“…For example, among brain tumors, glioblastoma, pilocytic astrocytoma, and pontine glioma can show gene fusions involving NTRK2 or NTRK3 [63,87,142,143]. A number of small-molecule acting as pan-Trk inhibitors are currently being evaluated in clinical trials [144][145][146]. A recent phase 1 and 2 clinical study examining the effects of the pan-Trk inhibitor larotrectinib in children and adults with various types of peripheral solid cancers harboring NTRK gene fusions found pronounced and durable responses regardless of patient age or tumor type [147].…”
Section: Discussionmentioning
confidence: 99%
“… 36 For instance, a selenium compound, PBISe, was found to be a chemotherapeutic agent in melanoma and human HCC. 37 However, it is still necessary to explore and develop more selenium antitumor drugs with low toxicity and strong target efficacy. In the present study, we identified that SeS 2 , a compound typically found in lotion form and mainly used to treat seborrheic dermatitis and tinea versicolor, induced growth inhibition and mitochondrial apoptosis of HCC cells in vitro and in vivo in a PLAGL2‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports on the anticancer activity of Se‐containing compounds, including organic, inorganic, natural, and synthetic molecules 36 . For instance, a selenium compound, PBISe, was found to be a chemotherapeutic agent in melanoma and human HCC 37 . However, it is still necessary to explore and develop more selenium antitumor drugs with low toxicity and strong target efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…STARTRK-2, in particular, includes patients with salivary gland tumours harbouring a NTRK3 gene fusion, similar to that in MASC. In addition to entrectinib and larotrectinib, which are two approved therapy options, other TRKIs, such as sitravatinib, cabozantinib, belizatinib, and several more, have been evaluated in clinical trials ( 29 ).…”
Section: Discussionmentioning
confidence: 99%